“Fuimos los primeros en apostar por una de las principales innovaciones en sistemas de información”. Investigación de las motivaciones de los pioneros españoles en XBRL: “We were the first to support a major is innovation”. Research into the motivations of spanish pioneers in XBRL - Escobar-Rodriguez, Tomas; Gago-Rodríguez, Susana (Revista de Contabilidad - Spanish Accounting Review, 2012)
We conduct a field study to analyse the reasons why pioneers supported the introduction of the Extensible Business Reporting Language (XBRL) from its earliest days in Spain. The Spanish pioneers were able to visualize the possibilities of the XBRL as an effective tool for facilitating the transmission of accounting and related information. At that point in time, innovators had available a limited amount of technical information on XBRL, because it was in the process of development. Hence, their engagement in the introduction of XBRL was based more on intuition than on in-depth knowledge of the technological advantages to be gained from its application. Further, their support for the innovation was active and not passive.